Kajian Morfometri Lereng Untuk Konservasi Tanah Di Kecamatan Jatiyoso Kabupaten Karanganyar - Hidayat, Muhammad Syarif, Ir. Taryono, Drs. Suharjo (2016)
This research was conducted in the Sub District Jatiyoso District Karanganyar entitled "Study Morphometry Slopes For Soil Conservation In Sub District Jatiyoso District Karanganyar", in order to determine morphometric slope causing geomorphological processes resulting erosion. In addition, also want to know other forms of soil conservation to reduce the occurrence of erosion processes in the study area. The method used in this study is a survey. The survey includes observation and measurement systematically, complemented by the use of secondary data analysis. The sampling technique using stratifed sampling strata land units, the captured data is data morphology, slope, slope length, slope shape, geomorphological processes, forms of conservation, and crop types. While the method of data analysis used is descriptive method. Based on the results of this study indicate that: The characteristics of geomorphology in the study area varies from unit of land that has a slope of the biggest V3 VI Ack Kb and V3 VI Ack Tg, namely 84%, while unit of land that has a slope smallest V4 V Lc Pm and V4 V Lck Pm, which is 9%. Erosion in the area of research that sheet erosion and gully erosion which contained nearly all the land units. And weathering that occurred in the study area almost all land units are heavy weathering. As for the rocks that make up the study area or Litologinya is Lawu Breccia lava rock, Lava and Tuff. Forms of conservation land in the study area is in the form of mechanical and vegetative methods. Conservation shape mechanically both in the form of construction of bench terraces, patio benches were construction, shoddy construction bench terraces, patio benches imperfect. While conservation methods vegetative form of annual plants and crops. With this research in the area Jatiyoso presented in map form morphoconservation a scale of 1: 70,000 and geomorphology map with a scale of 1: 70,000.